Challenges and outcomes of the double kissing crush stenting technique: Insights from the PROGRESS‐BIFURCATION registry. Issue 4 (23rd February 2022) - Simsek, Bahadir; Kostantinis, Spyridon; Karacsonyi, Judit; Vemmou, Evangelia; Nikolakopoulos, Ilias; Assali, Maen; Burke, M. Nicholas; Garcia, Santiago; Wang, Yale; Chavez, Ivan; Goessl, Mario; Sorajja, Paul; et al.
Abstract: Background: Although the double kissing (DK) crush stenting technique can provide excellent outcomes in percutaneous coronary intervention (PCI) of bifurcation lesions, it can be challenging to perform. Methods: We examined the clinical and angiographic characteristics, challenges encountered, and procedural outcomes of bifurcation PCI with DK crush in Prospective Global Registry of Percutaneous Coronary Intervention in Bifurcation Lesions (PROGRESS‐BIFURCATION, NCT05100992). Results: DK crush was used in 48 of 435 bifurcation lesions (11%). Technical success was 100%, procedural success was 96%, and the incidence of in‐hospital major adverse cardiovascular events was 4%. Challenges while performing DK crush were encountered in 26 lesions (54%): (1) difficulty in side branch (SB) first rewiring (38%) that was overcome with the use of a new guidewire (30%) or a microcatheter (15%); (2) inability to deliver balloon to an SB for the first kiss (54%) that was overcome with the use of a smaller balloon (86%), rewiring (29%), microcatheter (14%), and increased support 7%; (3) difficulty in SB second rewiring (19%) that was overcome with the use of a new guidewire (80%) and/or microcatheter (60%). DK crush was more often performed in left main and proximal left anterior descending artery lesions (70% vs. 50%, p  = 0.014). DK crush cases required more contrast (198 ± 84 ml vs. 163 ± 70 ml, p  = 0.003), fluoroscopy time (35 ± 20 min vs. 25 ± 21 min, p  = 0.004), and lasted longer (137 ± 69 min vs. 99 ± 66 min, p  = 0.001) compared with non‐DK crush techniques. Conclusions: While challenges are common when performing DK crush bifurcation stenting, success rates are high and complication rates are low.